Topical pimecrolimus in the treatment of genital lichen sclerosus. (October 2013) - Andreassi, Marco; Bilenchi, Roberta
Abstract : Pimecrolimus is a drug belonging to the class of macrolactamic immunosuppressants, similar to tacrolimus, and has been employed mainly in the treatment of atopic dermatitis, but is also active in other skin diseases, including genital lichen sclerosus (LS). The safety profile of pimecrolimus was the subject of special attention by the US FDA, which in 2005 issued a Public Health Advisory on the potential risk of cancer associated with the use of topical calcineurin inhibitors. However, many scientific societies have criticized the FDA note, referring to the vast literature on the subject in which there is no evidence available that topical use of the drug is dangerous. Patients with LS, of both sexes, may develop genital squamous cell carcinoma. This event, however, is not a contraindication to the use of pimecrolimus.